The 4th EWaS International Conference: Valuing the Water, Carbon, Ecological Footprints of Human Activities 2020
DOI: 10.3390/environsciproc2020002065
|View full text |Cite
|
Sign up to set email alerts
|

Micromixing Nanoparticles and Contaminated Water Under Different Velocities for Optimum Heavy Metal Ions Adsorption

Abstract: Effective mixing between contaminated water and nanoparticles is of great importance in various purification applications of microfluidics, especially when heavy metals are involved. Electromagnetic and shear mixing is combined here to explore optimization mixing strategies. A contaminated water stream is confined between two fresh-water streams loaded with nanoparticles and their mixing is studied numerically. The magnetic mixing is superimposed here with a time-modulated gradient external magnetic field. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Nanoparticles without magnetic properties have limited applicability in water purification due to the difficulty of separation from the aqueous solution [58]. Magnetic nanoparticles present advantages due to their large surface area, size, and shapedependent catalytic properties and can be separated from the aqueous solution with the use of a magnet field [48,59]; thus many methods have been investigated for their potential application in both environmental and biological fields [60][61][62].…”
Section: Heavymentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles without magnetic properties have limited applicability in water purification due to the difficulty of separation from the aqueous solution [58]. Magnetic nanoparticles present advantages due to their large surface area, size, and shapedependent catalytic properties and can be separated from the aqueous solution with the use of a magnet field [48,59]; thus many methods have been investigated for their potential application in both environmental and biological fields [60][61][62].…”
Section: Heavymentioning
confidence: 99%
“…The major advantage of computational water treatment methods compared with an experimental method is that the steps of synthesis and characterization of magnetic nanoparticles are not time-consuming since they do not exist. The aims of microfluidic mixing and driving simulations for water purification from heavy metal ions are to achieve rapid mixing and desired guidance of nanoparticles [48,51,59,358].…”
Section: Main Findings During the Last Decadementioning
confidence: 99%
“…where t is time and 𝑣 the kinematic viscosity of the water. Details of the numerical models, force, and moment terms used in the equations may be found in Refs [8,32]. The motion equations of each single particle in the discrete frame are based on the Newton law and may be presented as follows:…”
Section: Casementioning
confidence: 99%
“…There are several approaches to enhance the degree of mixing (DOM): complex three dimensional structures, modification of planar geometry, and manipulation of flow conditions. Using an unequal magnitude of inlet velocities is an example to control flow conditions [ 16 , 17 ]. For example, Karvelas et al [ 16 ] showed that a velocity ratio increase leads to an enhancement of mixing between the heavy metals and nanoparticles by the action of shear stress between them.…”
Section: Introductionmentioning
confidence: 99%
“…Using an unequal magnitude of inlet velocities is an example to control flow conditions [ 16 , 17 ]. For example, Karvelas et al [ 16 ] showed that a velocity ratio increase leads to an enhancement of mixing between the heavy metals and nanoparticles by the action of shear stress between them. Another example is to use a pulsatile inlet flow.…”
Section: Introductionmentioning
confidence: 99%